Surface Evolver Simulation of Droplet Wetting Morphologies on Fiber Without Gravity - Xu, Chengwei; Lu, Zhenyan; Li, Lirong (Frontiers in Energy Research, 2022)
Droplet wetting phenomenon is encountered in many engineering applications. Three wetting morphologies, namely, barrel, clamshell, and liquid bridge, are investigated by the finite element method, Surface Evolver (SE) simulations. The barrel shape shrinks gradually as contact angle increases. In the shrinkage process, the dimensionless wetting length reduces, and maximum diameter increases. As the increase of the contact angle, the gas–liquid contact line of clamshell droplets bends and contracts inward gradually. The geometry parameters are extracted from the results from simulations. In addition, the critical spacing of liquid bridge rupture is determined. The critical spacing increases rapidly with the expanding of liquid bridge volume. The liquid bridge volume has a significant effect on critical spacing.